KARAKTERISASI SIFAT FISIS PAPAN PARTIKEL SABUT KELAPASERAT PELEPAH LONTAR - Muh. Said. L; Nurul Fuadi; Muh. Fadhlan Dzikriansyah (JFT : Jurnal Fisika dan Terapannya, 2021)
This study aims to determine the results of testing on particle board made from coconut fiber and palm fronds; determine the effect of variations in the composition of the material on the quality of the physical properties of the material and determine whether the particleboard made has complied with the Indonesian National Standard SNI 03-2105 2006. The research method was carried out by laboratory testing consisting of three stages. Phase I: Preparation of materials and determination of mass and composition variations, Phase II: Process of making samples (finely chopped grinding phase, sifting 18 mesh, weighing according to composition variations, mixing, molding size (25×25×1) 3 cm, pressing at 185 °C for 15 minutes at a pressure of 25 kg/cm3 and standing 2 × 24 hours), and stage III: The process of testing physical properties includes moisture content, density, and thickness expansion. The results showed that the laboratory tests of physical properties: moisture content (2.01- 3.88)%, density (0.713-0.891) gr/cm3, and thickness expansion ranged from (0.75-11.61)%. Particleboard made based on its physical properties has complied with SNI 03-2105-2006.